A nanometer dual-phase high entropy zirconate material with nearly equal proportions and its preparation method and application
The preparation of nanobiphase high entropy zirconate materials through chemical precipitation method solves the problems of low thermal expansion coefficient and uneven component distribution in existing materials, and improves the high-temperature stability and mechanical properties of the materials, and is suitable for high-temperature thermal barrier coating applications.
Patent Information
- Application Number
- CN202510229557.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-28
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2045-02-28
AI Technical Summary
There are problems such as low thermal expansion coefficient and uneven component distribution in existing high entropy zirconate materials, which are difficult to meet the long-term application of thermal barrier coatings at high temperatures.
Nanobiphase high entropy zirconate materials are prepared by chemical precipitation method. By controlling the addition order of alloy elements and the precipitation reaction conditions, a uniform and stable tetramer structure is formed to avoid the degenerate aggregation of rare earth elements and improve the uniformity of component distribution.
It significantly improves the thermal expansion coefficient, mechanical properties and high-temperature phase stability of the material, and is suitable for thermal barrier coating materials serving at higher temperatures, improving the thermal insulation performance and stability of the coating.
Smart Images

Figure CN119707486B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of thermal barrier coating materials, and relates to a nanometer dual-phase high-entropy zirconate material with nearly equal proportions and low thermal conductivity, high thermal expansion coefficient, good mechanical properties and high-temperature stability, as well as a preparation method and application thereof. Background Art
[0002] Power units such as aircraft engines and gas turbines cover the most advanced technologies in aerodynamic system design, precision machining design, and advanced material manufacturing. They are an important standard for measuring a country's industrial manufacturing level and an important manifestation of a country's comprehensive national strength. With the continuous development of the aviation industry, the operating temperature of the hot end components of the engine continues to rise, and thermal barrier coating technology has emerged. Thermal barrier coatings have made great contributions to improving the high-temperature performance of key engine components and have become a key means to increase the operating temperature of the engine. Therefore, the research and development of thermal barrier coating materials is of great significance to the development of the aviation industry.
[0003] Faced with the harsh service environment of thermal barrier coatings, ordinary ceramic materials are difficult to meet their service requirements. As a thermal barrier coating material, it should have low thermal conductivity, high thermal expansion coefficient, low elastic modulus, high fracture toughness, good high-temperature phase stability and corrosion resistance. At present, the most widely used thermal barrier coating material is 6~8 wt. % Y2O3-ZrO2 (YSZ), but it will decompose into yttrium-rich phase and yttrium-poor phase above 1200℃, causing the coating to fail and difficult to be used for a long time at higher temperatures, which greatly limits the development of the aviation industry.
[0004] Rare earth zirconate materials have become one of the candidate material systems for thermal barrier coatings due to their lower thermal conductivity than YSZ and good corrosion resistance, but their mechanical / thermal properties are limited and cannot provide stable guarantees for the long service life of thermal barrier coatings. With the continuous development and improvement of high entropy ceramic systems, a large number of studies have confirmed that after a variety of excellent zirconate ceramics are designed through high entropy, the mechanical / thermal comprehensive properties of ceramic materials are usually better than those of single-component zirconates, making them have broad development potential in the field of high-temperature structural materials for aerospace. For example, China's authorized patent CN115925417B discloses a high entropy zirconate powder obtained by a high-temperature solid-phase reaction method using Gd2O3 powder, Er2O3 powder, Tm2O3 powder, Y2O3 powder, Yb2O3 powder and ZrO2 powder. This scheme designs a high-entropy rare earth zirconate composition so that a large proportion of spherical fluorite phase exists in the composite material, which makes the material have lower thermal conductivity and excellent resistance to CMAS corrosion. However, the high-temperature solid-phase reaction method it adopts is energy-intensive and cannot achieve mass production of high-entropy ceramic materials with uniform composition. In addition, the selected alloy composition has limited improvement on the thermal expansion coefficient and fracture toughness of the composite material, which limits the use of the material. Summary of the invention
[0005] In order to solve the problems of low thermal expansion coefficient and uneven component distribution in existing high entropy zirconate materials, the first purpose of the present invention is to provide a nano-duplex high entropy zirconate material with nearly equal proportions. Through the synergistic effect of alloy components and nearly equal duplex phases, the zirconate material exhibits extremely low thermal conductivity, extremely high thermal expansion coefficient, good mechanical properties and high temperature stability.
[0006] The second object of the present invention is to provide a method for preparing a nano-duplex high-entropy zirconate material with nearly equal proportions. By adopting a chemical precipitation method and controlling the order of adding alloy elements, a uniform and stable tetramer structure is formed, avoiding the occurrence of rare earth element segregation, making the components in the zirconate material evenly distributed, and significantly improving the comprehensive performance of the composite material.
[0007] The third object of the present invention is to provide an application of a nano-duplex high-entropy zirconate material with nearly equal proportions. The zirconate material of the present invention has extremely low thermal conductivity and extremely high thermal expansion coefficient, and is particularly suitable for being prepared into a ceramic material for use in surface coatings of hot end components of aircraft engines and gas turbines. It can significantly improve the thermal insulation performance of the coating and its stability and reliability under complex thermal cycle conditions.
[0008] In order to achieve the above technical objectives, the present invention provides a method for preparing a nano-duplex high-entropy zirconate material with nearly equal proportions. The method comprises the following steps: dissolving lanthanum oxide, neodymium oxide, gadolinium oxide, dysprosium oxide and ytterbium oxide in an acid solution respectively to obtain five single rare earth metal salt solutions; the five single rare earth metal salt solutions are sequentially added to a zirconium salt solution in the order of ion radius from large to small to form a mixed solution with a uniform and stable tetramer structure, and then a precipitant is added to carry out a precipitation reaction to obtain a gel-like precursor precipitate; the gel-like precursor precipitate is aged, dried and calcined at high temperature to obtain a high-entropy zirconate material.
[0009] The key to the technical solution of the present invention lies in the synergistic effect of the components and the preparation method. Specifically, the present invention selects light rare earths La, Nd and Gd with larger ionic radius and heavy rare earths Dy and Yb with smaller ionic radius. This element composition makes the size disorder of the high entropy zirconate system as high as 9.563%, forming a stable two-phase high entropy zirconate structure, in which the weight of the pyrochlore phase accounts for 43.77% and the fluorite phase accounts for 56.23%. The nearly equal-proportion nano-two-phase structure can significantly increase the content of heterogeneous interfaces in the material, which effectively improves the mechanical properties of the zirconate material, especially the fracture toughness. At the same time, the rare earth combination of La, Nd, Gd, Dy and Yb in the present invention makes the high entropy zirconate have a large relative molecular mass (602.06), a complex crystal structure, and contains a variety of nonlinear chemical bonds, which enhances the phonon scattering inside the material and reduces the mean free path of phonons, thereby making the thermal conductivity of the material low. In addition, the average electronegativity difference between anions and cations in the material is small (1.0998), and the electronegativity difference is negatively correlated with the thermal expansion coefficient. A smaller average electronegativity difference is conducive to improving the thermal expansion coefficient of the system, and the higher dimensional disorder formed by the combination of alloy elements will lead to greater lattice distortion, further improving the thermal expansion coefficient of the material. Most importantly, the alloy element combination of the present invention has a higher system entropy value while ensuring a higher atomic disorder distribution, so that a stable phase structure can be maintained under high temperature and long-term treatment.
[0010] On the other hand, compared with the high-temperature solid-phase synthesis method currently used for rare earth zirconate ceramic powders, which is prone to problems such as low powder purity, many impurities, large grain size and serious agglomeration, the chemical precipitation method used in the present invention can achieve molecular or atomic mixing of raw materials, and the synthesized powder has extremely high purity, nano-scale grain size, narrow size distribution and uniform particle size. In addition, the mixing order of each alloy element needs to be strictly controlled during the preparation process of the step-by-step precipitation method of the present invention, otherwise the rare earth element segregation phenomenon will occur. This is because zirconium oxychloride is mostly in the form of [Zr(OH)8(H2O) 16 ] 8+It exists in the form of a tetramer. The introduction of rare earth salt solution will affect the stability of the tetramer, and the rare earth ions will compete with zirconium ions for coordination. The salt solutions of La, Nd, Gd, Dy and Yb are introduced into the Zr salt solution in the order of ionic radius from large to small and electronegativity from low to high. The rare earth ions with larger ionic radius will not destroy the original structure of the tetramer too violently when competing with zirconium ions for coordination. Each rare earth ion is added after the previous rare earth ion has coordinated with the zirconium ion to a certain extent. This step-by-step process allows the tetramer structure to be gradually adjusted to adapt to the coordination requirements of the newly added rare earth ions to obtain a more uniform and stable tetramer structure, which is conducive to promoting the formation of a stable composite hydroxide network structure in the precursor, thereby promoting the uniform distribution of rare earth elements in the synthetic powder, and then improving the high-temperature phase stability and mechanical properties of the composite material.
[0011] As a preferred solution, the lanthanum oxide, neodymium oxide, gadolinium oxide, dysprosium oxide and ytterbium oxide are in powder form with a purity of ≥99.99%.
[0012] As a preferred solution, the acid solution includes hydrochloric acid and / or nitric acid; the present invention uses the acid solution mainly to dissolve the alloy oxides to form alloy elements.
[0013] As a preferred solution, the concentrations of the five single rare earth metal salt solutions are all 1-2 mol / L.
[0014] As a preferred solution, the concentration of the zirconium salt solution is 0.5-2 mol / L. Further, the zirconium salt solution includes ZrOCl2 with a purity of ≥98%.
[0015] As a preferred solution, the addition amount of the lanthanum oxide, neodymium oxide, gadolinium oxide, dysprosium oxide, ytterbium oxide and zirconium salt solution is measured according to the molar ratio of La, Nd, Gd, Dy, Yb and Zr being 1:1:1:1:1:5. Only when the molar ratio of each alloy element is selected in the present invention can the high entropy zirconate material with excellent comprehensive performance of the present invention be obtained.
[0016] As a preferred solution, the mixed solution and the precipitant are added dropwise synchronously during the precipitation reaction, and the pH of the precipitation reaction is maintained constant at 7 to 12 by adjusting the dropping speed of the precipitant solution. The present invention can maintain a constant pH value of the precipitation environment by adding the mixed solution and the precipitant dropwise synchronously to the mother solution containing the precipitant, further promoting the uniform distribution of the alloying elements, and the subsequent calcination process can dehydrate and transform the precursor at a low temperature, so that the material grain growth rate will not be too fast due to the excessively high synthesis temperature, thereby damaging its anti-sintering performance and mechanical properties.
[0017] As a preferred solution, the precipitant is composed of ammonia water and water in a volume ratio of 1: (1.5-2). The ammonia water used in the present invention is weakly alkaline, which can provide a stable pH environment and play a buffering role, preventing drastic changes in pH value, which is conducive to the precipitation reaction.
[0018] As a preferred solution, the precipitation reaction is carried out at room temperature.
[0019] As a preferred solution, the aging time is 12 to 24 hours, and the ball milling rate is 150 to 300 r / min for 2 to 4 hours. Aging the precursor precipitate can promote the full formation of the composite hydroxide polymer composed of the rare earth and zirconium hydroxides, and ball milling can fully mix the various raw materials, reduce component agglomeration, ensure uniform distribution of components, and facilitate the subsequent calcination process.
[0020] As a preferred solution, the drying is staged drying, and further preferably, the staged drying is divided into two stages of drying, the first stage drying temperature is 80-90°C, the time is 10-15h, and the second stage drying temperature is 120-150°C, the time is 10-12h. The present invention removes the anhydrous ethanol introduced in the washing process by first low-temperature drying, and then removes the free water and adsorbed water in the precursor by high-temperature drying. And the agglomeration of the precursor powder can be reduced by staged drying.
[0021] As a preferred solution, the high temperature calcination conditions are: 600-1600°C for 4-6 hours. More preferably, the calcination temperature is 1000-1400°C.
[0022] The present invention provides a method for preparing a nanometer dual-phase high-entropy zirconate material with nearly equal proportions, which specifically comprises the following steps:
[0023] S1. The amount of oxide is calculated according to the molar ratio of the elements in the target high entropy zirconate material. The corresponding amount of La2O3 powder, Nd2O3 powder, Gd2O3 powder, Dy2O3 powder and Yb2O3 powder are dissolved in nitric acid and / or hydrochloric acid respectively by a step-by-step method to promote the full dissolution of the rare earth oxides, and finally five single rare earth oxide salt solutions are obtained. The ion concentration of each salt solution is recorded as S A ; The S A The concentration is 1-2 mol / L, more preferably 1-1.5 mol / L.
[0024] S2. Calculate the amount of ZrOCl2•8H2O according to the molar ratio of Zr in the target high entropy zirconate material, weigh the corresponding amount of ZrOCl2•8H2O, and dissolve it in water to obtain a zirconium salt solution, recorded as S B ; The SB The concentration of zirconium ions is 1 to 2 mol / L, more preferably 1 to 1.5 mol / L.
[0025] S3, sequentially mix the salt solutions of La, Nd, Gd, Dy and Yb A Join S B Mix and stir thoroughly to obtain a cationic mixed solution, then add water to make up the volume, which is recorded as S C ; The S C The total concentration of the neutral cations is 0.5 to 2 mol / L, more preferably 1 to 1.5 mol / L.
[0026] S4, measure ammonia water and dilute it with water to obtain a precipitant solution, recorded as S D ; The S D The volume ratio of ammonia water to water in the solution is 1:(1.5~2).
[0027] S5, the precipitant S D The solution was titrated into a certain amount of base solution, and the pH value was adjusted to the target value; then S C and S D Titrate into the base solution simultaneously, and adjust S D The flow rate is kept constant to maintain the pH value of the precipitation environment; stirring is continued until the titration process is completed to obtain a gel precursor precipitate, which is recorded as S E ; The volume of the mother liquor is 200~400ml, more preferably 300~350ml; the pH value range is 7~12, preferably 9~10.
[0028] S6, the colloidal precipitate S E Aging, washing, drying and ball milling to obtain a precursor powder, wherein the aging time is 12-24 hours, the washing times are 6-10 times, preferably 7-8 times, the drying temperature is 80-90° C. for 10-15 hours, and then 120-150° C. for 10-12 hours, and the ball milling speed is 150-300 r / min, preferably 200-250 r / min.
[0029] S7. calcining the precursor powder in an air atmosphere for 4 to 6 hours to obtain a nanoscale high entropy zirconate powder material; the calcination temperature is 600 to 1600°C, and more preferably 1000 to 1400°C.
[0030] The present invention also provides a nanometer dual-phase high entropy zirconate material with a nearly equal ratio, the chemical formula of which is (La 0.2 Nd 0.2 G 0.2 Dy 0.2 Yb 0.2)2Zr2O7, having a pyrochlore phase and a fluorite phase in nearly equal weight proportions. The nearly equal weight proportion distribution of the pyrochlore phase and the fluorite phase in the zirconate material of the present invention can significantly increase the content of the heterogeneous interface in the material, which effectively improves the mechanical properties of the zirconate material, especially the fracture toughness.
[0031] Finally, the present invention also provides an application of a nanometer dual-phase high entropy zirconate material with nearly equal proportions, which is prepared into a ceramic material for use in the surface coating of hot end components of aircraft engines and gas turbines. The zirconate material of the present invention has extremely low thermal conductivity and extremely high thermal expansion coefficient, and is particularly suitable for being prepared into a ceramic material for use in the surface coating of hot end components of aircraft engines and gas turbines, which can significantly improve the thermal insulation performance of the coating and the stability and reliability under complex thermal cycle conditions.
[0032] As a preferred scheme, the preparation process of the ceramic material is: the high entropy zirconate material is obtained by PVA granulation, screening, molding and sintering; wherein the amount of PVA added is 1~8% of the mass of the high entropy zirconate material; the molding pressure is 15~20MPa, the pressurizing time is 100~120s, the sintering temperature is 1500~1650℃, and the time is 8~10h.
[0033] Compared with the prior art, the present invention has the following beneficial effects:
[0034] (1) The present invention (La 0.2 Nd 0.2 G 0.2 Dy 0.2 Yb 0.2 )2Zr2O7 high entropy zirconates have lower thermal conductivity than medium entropy zirconates and single rare earth zirconates (1.19~0.97W·m at room temperature to 1100℃) -1 ×K -1 ), higher thermal expansion coefficient (11.63×10 -6 K -1 (1200℃) and phase stability (treated at 1600℃ for 10h)), as well as better mechanical properties (fracture toughness up to 1.53MPa•m 1 / 2 ), suitable for service under higher temperature conditions, and conducive to improving the thermal cycle service life of thermal barrier coatings. The high entropy zirconate material can be used to prepare thermal barrier coatings on the surfaces of hot end components of aircraft engines and gas turbines.
[0035] (2) The present invention selects light rare earths La, Nd and Gd with larger ionic radius and heavy rare earths Dy and Yb with smaller ionic radius, so as to make the size disorder of the high entropy zirconate system as high as 9.563%, and form a stable nearly equal-proportional two-phase high entropy zirconate structure, which significantly increases the content of heterogeneous interfaces in the material, and effectively improves the mechanical properties of the zirconate material, especially the fracture toughness. In addition, the electronegativity difference in the designed material is only 1.098, which synergistically improves the thermal expansion coefficient of the material, which is much higher than that of the existing high entropy zirconate materials.
[0036] (3) The present invention adopts a step-by-step precipitation method, and introduces the salt solutions of La, Nd, Gd, Dy and Yb into the Zr salt solution in the order of ionic radius from large to small and electronegativity from low to high. When the rare earth ions with larger ionic radius compete with zirconium ions for coordination, they will not destroy the original structure of the tetramer too violently. Each rare earth ion is added after the previous rare earth ion has coordinated with the zirconium ion to a certain extent. This step-by-step process allows the tetramer structure to be gradually adjusted to adapt to the coordination requirements of the newly added rare earth ions, so that a more uniform and stable tetramer structure can be obtained, avoiding the segregation of rare earth elements in the material, which is conducive to promoting the formation of a stable composite hydroxide network structure in the precursor, thereby promoting the uniform distribution of rare earth elements in the synthetic powder, and then improving the high-temperature phase stability and mechanical properties of the composite material. At the same time, it also avoids the practice of adding a dispersant to promote the uniform distribution of the alloy in the prior art.
[0037] (4) The synthesis method of the present invention can achieve mixing of raw materials at the molecular or atomic level. The synthesized powder has extremely high purity, a grain size of 10 to 100 nm, and a uniform particle size. It has low equipment requirements, controllable composition, a short preparation cycle, and low cost. It can achieve stable batch synthesis of high-entropy zirconate powders with precisely controllable composition at low temperatures.
[0038] (5) This method has strong process adaptability and can achieve stable synthesis and low-cost preparation of small batches of high-entropy zirconate materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 (La prepared in Example 1 0.2 Nd 0.2 G 0.2 Dy 0.2 Yb 0.2 )XRD pattern of 2Zr2O7 powder.
[0040] Figure 2 (La prepared in Example 1 0.2 Nd 0.2 G 0.2 Dy 0.2 Yb 0.2)TEM image of 2Zr2O7 powder.
[0041] Figure 3 (La prepared in Example 1 0.2 Nd 0.2 G 0.2 Dy 0.2 Yb 0.2 )XRD pattern of 2Zr2O7 ceramics.
[0042] Figure 4 (La prepared in Example 1 0.2 Nd 0.2 G 0.2 Dy 0.2 Yb 0.2 )TEM image and surface distribution map of 2Zr2O7 ceramic slice.
[0043] Figure 5 For the comparative example 1 prepared (La 1 / 3 G 1 / 3 Yb 1 / 3 )TEM image and surface distribution map of 2Zr2O7 ceramic slice.
[0044] Figure 6 For the comparative example 2 prepared (La 1 / 3 G 1 / 3 Yb 1 / 3 )SEM image and surface distribution map of 2Zr2O7 ceramic slice.
[0045] Figure 7 (La prepared in Example 1 and Comparative Example 1 0.2 Nd 0.2 G 0.2 Dy 0.2 Yb 0.2 )2Zr2O7 ceramics and (La 1 / 3G 1 / 3 Yb 1 / 3 )Comparison of heat capacity, thermal diffusion coefficient and thermal conductivity of 2Zr2O7 ceramics.
[0046] Figure 8 (La prepared in Example 1 and Comparative Example 1 0.2 Nd 0.2 G 0.2 Dy 0.2 Yb 0.2 )2Zr2O7 ceramics and (La 1 / 3G 1 / 3 Yb 1 / 3 )Comparison of linear shrinkage and thermal expansion coefficients of 2Zr2O7 ceramics.
[0047] Fig. 9(La prepared in Example 1 0.2 Nd 0.2 G 0.2 Dy 0.2 Yb 0.2 )Elastic modulus and fracture toughness of 2Zr2O7 ceramics. DETAILED DESCRIPTION
[0048] In order to further illustrate the present invention, the contents of the present invention are described in detail below in conjunction with the examples. However, it should be understood that these examples are implemented on the premise of the technical solution of the present invention, and detailed implementation methods and specific operating processes are given only to further illustrate the features and advantages of the present invention, rather than to limit the claims of the present invention. The protection scope of the present invention is not limited to the following examples.
[0049] Example 1
[0050] (1) Weigh equimolar amounts of La2O3 powder, Nd2O3 powder, Gd2O3 powder, Dy2O3 powder and Yb2O3 powder, respectively, place them in hydrochloric acid, and stir and heat until the rare earth oxide powder is fully dissolved to obtain five single rare earth salt solutions; after cooling, add deionized water to the five rare earth salt solutions to dilute them to a rare earth ion concentration of 1.5 mol / L, which is recorded as solution S A ;
[0051] (2) According to the molar ratio of RE:Zr of 1:1, weigh the corresponding amount of ZrClO2·8H2O and dissolve it in deionized water to a Zr concentration of 1.5 mol / L, which is recorded as solution S B ;
[0052] (3) Sequentially mix the salt solutions S of La, Nd, Gd, Dy and Yb A Join S B The mixture was mixed and stirred thoroughly to obtain a cationic mixed solution, and then a certain amount of deionized water was added to make the volume to a metal ion concentration of 1.5 mol / L, which was recorded as S C ;
[0053] (4) Prepare a precipitant solution according to the volume ratio of ammonia water: deionized water = 1:1.5, and prepare a precipitant solution according to twice the standard reaction amount of hydrochloric acid and metal ions, denoted as S D ;
[0054] (5) By adding a small amount of S to 200 ml of the base solution D , adjust the pH to 9.5. Then add S C and S D At the same time, titrate it into the base solution and adjust S DThe flow rate was kept constant at 9.5 for the bottom solution, and stirring was continued during the titration process. Finally, a gel-like precursor precipitate was obtained, which was recorded as S E ; Wherein, the base liquid is deionized water;
[0055] (6) Precipitate the precursor S E After aging for 24 h, the precipitate was washed 6 times with deionized water and then dehydrated twice with anhydrous ethanol to obtain a pure precursor colloid.
[0056] (7) Drying the pure precursor colloid at 85°C for 10 h, drying at 120°C for 10 h, and then ball milling it at 200 r / min for 2 h to obtain a precursor powder;
[0057] (8) The precursor powder is calcined at 1400°C for 6 hours in an air atmosphere to obtain a nanoscale dual-phase high-entropy zirconate powder material. The size of the obtained high-entropy zirconate powder is between 10 and 100 nm and has extremely high purity.
[0058] (9) Polyvinyl alcohol (3% by mass) was added as a binder to the synthesized high entropy zirconate powder for granulation. The powder was then sieved through a 100-mesh screen and then pressurized at 15 MPa for 120 s to obtain a high entropy zirconate green body. The high entropy zirconate ceramic was sintered at 1600 °C for 10 h for thermal / mechanical properties testing.
[0059] The thermal conductivity of the high entropy zirconate ceramic is 1.19~0.97 W·m -1 ·K -1 (Room temperature to 1100°C), thermal expansion coefficient is 11.63×10 -6 K -1 (~1200℃), modulus as low as 167.59GPa, fracture toughness of 1.53MPa·m 1 / 2 , it can maintain a stable phase structure at 1600℃, and this material can meet the material selection requirements for thermal barrier coatings.
[0060] Example 2
[0061] (1) Weigh equimolar amounts of La2O3 powder, Nd2O3 powder, Gd2O3 powder, Dy2O3 powder and Yb2O3 powder, respectively, place them in hydrochloric acid, and stir and heat until the rare earth oxide powder is fully dissolved to obtain five single rare earth salt solutions; after cooling, add deionized water to the five rare earth salt solutions to dilute them to a rare earth ion concentration of 1 mol / L, which is recorded as solution S A ;
[0062] (2) According to the molar ratio of RE:Zr of 1:1, weigh the corresponding amount of ZrClO2·8H2O and dissolve it in deionized water to a Zr concentration of 1 mol / L, which is recorded as solution SB ;
[0063] (3) Sequentially mix the salt solutions S of La, Nd, Gd, Dy and Yb A Join S B The mixture was mixed and stirred thoroughly to obtain a cationic mixed solution, and then a certain amount of deionized water was added to make the volume to a metal ion concentration of 1 mol / L, which was recorded as S C ;
[0064] (4) Prepare a precipitant solution according to the volume ratio of ammonia water: deionized water = 1:2, and prepare a precipitant solution according to twice the standard reaction amount of hydrochloric acid and metal ions, denoted as S D ;
[0065] (5) By adding a small amount of S to 400 ml of the base solution D , adjust the pH to 11. Then S C and S D At the same time, titrate it into the base solution and adjust S D The flow rate was kept constant at 11 for the bottom solution pH value. Stirring was continued during the titration process. Finally, a gel precursor precipitate was obtained, which was recorded as S E ; Wherein, the base liquid is deionized water;
[0066] (6) Precipitate the precursor S E After aging for 18 h, the precipitate was washed 8 times with deionized water and then dehydrated twice with anhydrous ethanol to obtain a pure precursor colloid.
[0067] (7) Drying the pure precursor colloid at 85°C for 10 h, drying at 120°C for 10 h, and then ball milling it at 200 r / min for 2 h to obtain a precursor powder;
[0068] (8) The precursor powder is calcined at 1600°C for 6 hours in an air atmosphere to obtain a nanoscale dual-phase high-entropy zirconate powder material. The size of the obtained high-entropy zirconate powder is 100-200 nm and has extremely high purity.
[0069] (9) Polyvinyl alcohol (3% by mass) was added to the synthesized high entropy zirconate powder as a binder to form granules, which were then sieved through a 100-mesh sieve and then pressurized at 15 MPa for 120 s to obtain a high entropy zirconate green body. The green body was sintered at 1600 °C for 10 h to obtain a dense high entropy zirconate ceramic.
[0070] The thermal conductivity of the high entropy zirconate ceramics synthesized in this example is 1.30~1.05W·m -1 ·K -1 (Room temperature to 1100°C), thermal expansion coefficient is 11.55×10 -6 K -1(~1200℃), modulus is 170.62GPa, fracture toughness is 1.48MPa·m 1 / 2 , a stable phase structure can be maintained at 1600℃.
[0071] Example 3
[0072] (1) Weigh 8 mol of La2O3 powder, Nd2O3 powder, Gd2O3 powder, Dy2O3 powder and Yb2O3 powder respectively, place them in hydrochloric acid, and stir and heat until the rare earth oxide powder is fully dissolved to obtain five single rare earth salt solutions; after cooling, add deionized water to the five rare earth salt solutions to dilute them to a rare earth ion concentration of 1.5 mol / L, which is recorded as solution S A ;
[0073] (2) Weigh 40 mol of ZrClO2·8H2O and dissolve it in deionized water to a Zr concentration of 1.5 mol / L, which is referred to as solution S. B ;
[0074] (3) Sequentially mix the salt solutions S of La, Nd, Gd, Dy and Yb A Join S B The mixture was mixed and stirred thoroughly to obtain a cationic mixed solution, and then a certain amount of deionized water was added to make the volume to a metal ion concentration of 1.5 mol / L, which was recorded as S C ;
[0075] (4) Prepare a precipitant solution according to the volume ratio of ammonia water: deionized water = 1:1.5, and prepare a precipitant solution according to twice the standard reaction amount of hydrochloric acid and metal ions, denoted as S D ;
[0076] (5) By adding a small amount of S to 10L of the base solution D , adjust the pH to 9.5. Then add S C and S D At the same time, titrate it into the base solution and adjust S D The flow rate was kept constant at 9.5 for the bottom solution, and stirring was continued during the titration process. Finally, a gel-like precursor precipitate was obtained, which was recorded as S E ; Wherein, the base liquid is deionized water;
[0077] (6) Precipitate the precursor S E After aging for 24 h, the precipitate was washed 6 times with deionized water and then dehydrated twice with anhydrous ethanol to obtain a pure precursor colloid.
[0078] (7) Drying the pure precursor colloid at 85°C for 10 h, drying at 120°C for 10 h, and then ball milling it at 200 r / min for 2 h to obtain a precursor powder;
[0079] (8) The precursor powder is calcined at 1400°C for 6 hours in an air atmosphere to obtain a nanoscale dual-phase high-entropy zirconate powder material. The size of the obtained high-entropy zirconate powder is 20-150 nm and has extremely high purity.
[0080] Under this process condition, 12 kg of (La 0.2 Nd 0.2 G 0.2 Dy 0.2 Yb 0.2 )2Zr2O7 zirconate, achieving (La 0.2 Nd 0.2 G 0.2 Dy 0.2 Yb 0.2 )2Zr2O7 zirconate powder was prepared in small batches. The synthesized powder has extremely high purity, stable structure, and slightly increased grain size of 20~150 nm.
[0081] The thermal conductivity of the batch synthesized high entropy zirconate ceramic material in this embodiment is 1.23~0.92W·m -1 ·K -1 (Room temperature to 1100°C), the thermal expansion coefficient is 11.59×10 -6 K -1 (~1200℃), modulus is 169.32GPa, fracture toughness is 1.50MPa·m 1 / 2 , it can still maintain a stable phase structure after sintering at 1600℃ for 200h, which can meet the material selection requirements of thermal barrier coatings.
[0082] Comparative Example 1
[0083] (1) Weigh equimolar amounts of La2O3 powder, Gd2O3 powder, and Yb2O3 powder, respectively, place them in hydrochloric acid, and stir and heat until the rare earth oxide powder is fully dissolved to obtain three single rare earth salt solutions; after cooling, add deionized water to the three rare earth salt solutions to dilute them to a rare earth ion concentration of 1.5 mol / L, which is recorded as solution S A ;
[0084] (2) According to the molar ratio of RE:Zr of 1:1, weigh the corresponding amount of ZrClO2·8H2O and dissolve it in deionized water to a Zr concentration of 1.5 mol / L, which is recorded as solution S B ;
[0085] (3) Sequentially mix the salt solutions S of La, Gd and YbA Join S B The mixture was mixed and stirred thoroughly to obtain a cationic mixed solution, and then a certain amount of deionized water was added to make the volume to a metal ion concentration of 1.5 mol / L, which was recorded as S C ;
[0086] (4) Prepare the precipitant solution according to the volume ratio of ammonia water: deionized water = 1:1.5, denoted as S D ;
[0087] (5) By adding a small amount of S to 200 ml of the base solution D , adjust the pH to 9.5. Then add S C and S D At the same time, titrate it into the base solution and adjust S D The flow rate was kept constant at 9.5 for the bottom solution, and stirring was continued during the titration process. Finally, a gel-like precursor precipitate was obtained, which was recorded as S E ; Wherein, the base liquid is deionized water;
[0088] (6) Precipitate the precursor S E After aging for 24 h, the precipitate was washed 6 times with deionized water and then dehydrated twice with anhydrous ethanol to obtain a pure precursor colloid.
[0089] (7) Drying the pure precursor colloid at 85°C for 10 h, drying at 120°C for 10 h, and then ball milling it at 200 r / min for 2 h to obtain a precursor powder;
[0090] (8) The precursor powder was calcined at 1400 °C in air for 6 h to obtain a dual-phase structure (La 1 / 3G 1 / 3 Yb 1 / 3 )2Zr2O7 medium entropy zirconate powder material. The size of the obtained medium entropy zirconate powder is 30~120nm and has extremely high purity.
[0091] (9) 3% polyvinyl alcohol was added as a binder to the synthesized medium entropy zirconate powder to form granules, which were then sieved through a 100-mesh screen and then pressurized at 15 MPa for 120 s to obtain a high entropy zirconate green body. The green body was sintered at 1600 °C for 10 h to obtain (La 1 / 3G 1 / 3 Yb 1 / 3 )2Zr2O7 medium entropy zirconate ceramics.
[0092] The thermal conductivity of the medium entropy zirconate ceramic is 1.70~1.45 W·m -1 ·K -1 (Room temperature to 1100°C), thermal expansion coefficient is 10.50×10 -6 K-1 (~1200℃), modulus is 175.43GPa, fracture toughness is 1.30MPa·m 1 / 2 .
[0093] Comparative Example 2
[0094] (1) Weigh equimolar amounts of La2O3 powder, Nd2O3 powder, Gd2O3 powder, Dy2O3 powder and Yb2O3 powder, respectively, place them in hydrochloric acid, and stir and heat until the rare earth oxide powder is fully dissolved to obtain five single rare earth salt solutions; after cooling, add deionized water to the five rare earth salt solutions to dilute them to a rare earth ion concentration of 1.5 mol / L, which is recorded as solution S A ;
[0095] (2) According to the molar ratio of RE:Zr of 1:1, weigh the corresponding amount of ZrClO2·8H2O and dissolve it in deionized water to a Zr concentration of 1.5 mol / L, which is recorded as solution S B ;
[0096] (3) Sequentially add the salt solutions S of Yb, Dy, Gd, Nd and La rare earths A Join S B The mixture was mixed and stirred thoroughly to obtain a cationic mixed solution, and then a certain amount of deionized water was added to make the volume to a metal ion concentration of 1.5 mol / L, which was recorded as S C ;
[0097] (4) Prepare a precipitant solution according to the volume ratio of ammonia water: deionized water = 1:1.5, and prepare a precipitant solution according to twice the standard reaction amount of hydrochloric acid and metal ions, denoted as S D ;
[0098] (5) By adding a small amount of S to 200 ml of the base solution D , adjust the pH to 9.5. Then add S C and S D At the same time, titrate it into the base solution and adjust S D The flow rate was kept constant at 9.5 for the bottom solution, and stirring was continued during the titration process. Finally, a gel-like precursor precipitate was obtained, which was recorded as S E ; Wherein, the base liquid is deionized water;
[0099] (6) Precipitate the precursor S E After aging for 24 h, the precipitate was washed 6 times with deionized water and then dehydrated twice with anhydrous ethanol to obtain a pure precursor colloid.
[0100] (7) Drying the pure precursor colloid at 85°C for 10 h, drying at 120°C for 10 h, and then ball milling it at 200 r / min for 2 h to obtain a precursor powder;
[0101] (8) The precursor powder was calcined at 1400°C for 6 h in an air atmosphere to obtain a nanoscale dual-phase high-entropy zirconate powder material. The size of the obtained high-entropy zirconate powder is 20~100nm and has extremely high purity.
[0102] (9) Polyvinyl alcohol (3% by mass) was added as a binder to the synthesized high entropy zirconate powder for granulation. The powder was then sieved through a 100-mesh screen and then pressurized at 15 MPa for 120 s to obtain a high entropy zirconate green body. The high entropy zirconate ceramic was sintered at 1600 °C for 10 h for thermal / mechanical properties testing.
[0103] Compared with Example 1, the comparative example does not add the rare earth elements in the order of ion radius from large to small, and the synthesized high entropy zirconate material has a certain degree of rare earth element segregation, and its thermal conductivity is 1.23~1.01W·m -1 ·K -1 (Room temperature to 1100°C), thermal expansion coefficient is 11.52×10 -6 K -1 (~1200℃), modulus is 168.65GPa, fracture toughness is 1.50MPa·m 1 / 2 .
[0104] Comparative Example 3
[0105] (1) Weigh a certain amount of Yb2O3 powder, place it in hydrochloric acid, and stir and heat until the Yb2O3 powder is fully dissolved to obtain Yb 3+ After cooling, add deionized water to dilute to a rare earth ion concentration of 1.5 mol / L, which is called solution S A ;
[0106] (2) According to the molar ratio of Yb:Zr of 1:1, weigh the corresponding amount of ZrClO2·8H2O and dissolve it in deionized water to a Zr concentration of 1.5 mol / L, which is recorded as solution S B ;
[0107] (3) S A and S B Mix and stir thoroughly to obtain a cationic mixed solution, and then add a certain amount of deionized water to make the volume to a metal ion concentration of 1.5 mol / L, which is recorded as S C ;
[0108] (4) Prepare a precipitant solution according to the volume ratio of ammonia water: deionized water = 1:1.5, and prepare a precipitant solution according to twice the standard reaction amount of hydrochloric acid and metal ions, denoted as S D ;
[0109] (5) By adding a small amount of S to 200 ml of the base solution D , adjust the pH to 9.5. Then add S C and S D At the same time, titrate it into the base solution and adjust S D The flow rate was kept constant at 9.5 for the bottom solution, and stirring was continued during the titration process. Finally, a gel-like precursor precipitate was obtained, which was recorded as S E ; Wherein, the base liquid is deionized water;
[0110] (6) Precipitate the precursor S E After aging for 24 h, the precipitate was washed 6 times with deionized water and then dehydrated twice with anhydrous ethanol to obtain a pure precursor colloid.
[0111] (7) Drying the pure precursor colloid at 85°C for 10 h, drying at 120°C for 10 h, and then ball milling it at 200 r / min for 2 h to obtain a precursor powder;
[0112] (8) The precursor powder is calcined at 1400°C for 6 hours in an air atmosphere to obtain fluorite structured nano Yb2Zr2O7 powder. The size of the obtained ytterbium zirconate powder is 30-150nm and has extremely high purity.
[0113] (9) 3% by mass of polyvinyl alcohol was added as a binder to the synthesized Yb2Zr2O7 powder for granulation, which was then sieved through a 100-mesh sieve and then pressurized at 15 MPa for 120 s to obtain a high-entropy zirconate green body. The Yb2Zr2O7 ceramic was sintered at 1600°C for 10 h.
[0114] The single-component Yb2Zr2O7 material synthesized in this comparative example is a single fluorite structure, and its thermal conductivity is relatively high, 1.60~1.35W·m -1 ·K -1 (Room temperature to 1100°C), the thermal expansion coefficient is only 10.70×10 -6 K -1 (~1200℃).
[0115] Figure 1 The (La prepared in Example 1 is shown 0.2 Nd 0.2 G 0.2 Dy 0.2 Yb 0.2 )2Zr2O7 powder XRD pattern, (La 0.2 Nd0.2 G 0.2 Dy 0.2 Yb 0.2 )2Zr2O7 powder is extremely pure and consists of two structures: fluorite and pyrochlore. The weight of the pyrochlore phase accounts for 43.77% and the weight of the fluorite phase accounts for 56.23%.
[0116] Figure 2 The (La prepared in Example 1 is shown 0.2 Nd 0.2 G 0.2 Dy 0.2 Yb 0.2 )TEM image of Zr2O7 powder, the powder is nano-scale powder with a size of 10~100 nm.
[0117] Figure 3 The (La prepared in Example 1 is shown 0.2 Nd 0.2 G 0.2 Dy 0.2 Yb 0.2 )2Zr2O7 ceramics maintain a stable dual-phase structure after sintering and have good high-temperature phase stability.
[0118] Figure 4 The (La prepared in Example 1 is shown 0.2 Nd 0.2 G 0.2 Dy 0.2 Yb 0.2 )2Zr2O7 ceramic slice TEM image and surface distribution diagram, it can be seen that the rare earth elements are evenly distributed in the ceramic. According to the present invention, the step-by-step dissolution of rare earth oxides and mixing in the order of ion radius from large to small are conducive to promoting the uniform distribution of rare earth elements in the final synthesized zirconate.
[0119] Figure 5 The (La 1 / 3 G 1 / 3 Yb 1 / 3 ) TEM image and surface distribution diagram of 2Zr2O7 ceramic slices show that the distribution of each rare earth element in the ceramic is different. Compared with Example 1, the reduction of system entropy value leads to uneven distribution of light rare earth La and heavy rare earth Yb.
[0120] Figure 6 The (La 0.2 Nd 0.2 G 0.2 Dy 0.2 Yb 0.2)2Zr2O7 ceramic surface distribution diagram, it can be seen that the distribution of each rare earth element in the ceramic has a certain degree of segregation, and the ceramic slice SEM is quite different from that of Example 1. This is because the order of adding rare earth salt solution will affect the formation of the precursor, thereby affecting the final rare earth element distribution.
[0121] Figure 7 The (La prepared in Example 1 and Comparative Example 1 are shown. 0.2 Nd 0.2 G 0.2 Dy 0.2 Yb 0.2 )2Zr2O7 ceramics and (La 1 / 3 G 1 / 3 Yb 1 / 3 )Comparison of heat capacity, thermal diffusion coefficient and thermal conductivity of 2Zr2O7 ceramics shows that the high entropy ceramic has lower thermal conductivity than the medium entropy ceramic and has better thermal insulation effect.
[0122] Figure 8 The (La prepared in Example 1 and Comparative Example 1 are shown. 0.2 Nd 0.2 G 0.2 Dy 0.2 Yb 0.2 )2Zr2O7 ceramics and (La 1 / 3 G 1 / 3 Yb 1 / 3 )Comparison of linear contraction and thermal expansion coefficient of 2Zr2O7 ceramics. The high entropy ceramic has a higher thermal expansion coefficient than the medium entropy ceramic and can better match the alloy matrix.
[0123] Fig. 9 The (La prepared in Example 1 is shown 0.2 Nd 0.2 G 0.2 Dy 0.2 Yb 0.2 )The elastic modulus and fracture toughness of 2Zr2O7 ceramics. The lower elastic modulus and higher fracture toughness are helpful to improve the thermal cycling service life of thermal barrier coatings.
[0124] In summary, (La 0.2 Nd 0.2 G 0.2 Dy 0.2 Yb 0.2)2Zr2O7 high entropy zirconate has lower thermal conductivity, higher thermal expansion coefficient and phase stability, and better mechanical properties than medium entropy zirconate and single rare earth zirconate. It is suitable for service under higher temperature conditions and is beneficial to improve the thermal cycle service life of thermal barrier coatings. The high entropy zirconate material can be used to prepare thermal barrier coatings on the surfaces of hot end components of aircraft engines and gas turbines. The step-by-step rare earth introduction method is beneficial to promote the uniform distribution of rare earth elements in the synthetic powder. The preparation method of the present invention has low equipment requirements, controllable ingredients, short preparation cycle and low cost, and can achieve stable batch synthesis of high entropy zirconate powders with precisely controllable ingredients at low temperatures.
Claims
1. A method for preparing a nanometer dual-phase high entropy zirconate material with nearly equal proportions, characterized in that: Lanthanum oxide, neodymium oxide, gadolinium oxide, dysprosium oxide and ytterbium oxide are dissolved in acid solution respectively to obtain five single rare earth metal salt solutions; the five single rare earth metal salt solutions are added to the zirconium salt solution in the order of ion radius from large to small to form a mixed solution with a uniform and stable tetramer structure, and then a precipitant is added to carry out precipitation reaction to obtain a gel precursor precipitate; the gel precursor precipitate is aged, ball milled and calcined at high temperature to obtain a high entropy zirconate material.
2. The method for preparing a nanometer dual-phase high entropy zirconate material with nearly equal proportions according to claim 1, characterized in that: The acid solution includes hydrochloric acid and / or nitric acid; The concentrations of the five single rare earth metal salt solutions are all 1-2 mol / L; The concentration of the zirconium salt solution is 0.5-2 mol / L.
3. The method for preparing a nanometer dual-phase high entropy zirconate material with nearly equal proportions according to claim 1 or 2, characterized in that: The added amounts of the lanthanum oxide, neodymium oxide, gadolinium oxide, dysprosium oxide, ytterbium oxide and zirconium salt solution are measured according to a molar ratio of La, Nd, Gd, Dy, Yb and Zr of 1:1:1:1:1:
5.
4. The method for preparing a nanometer dual-phase high entropy zirconate material with nearly equal proportions according to claim 3, characterized in that: During the precipitation reaction, the mixed solution and the precipitant are added dropwise synchronously, and the pH of the precipitation reaction is maintained constant at 7-12 by adjusting the dropping speed of the precipitant solution.
5. The method for preparing a nanometer dual-phase high entropy zirconate material with nearly equal proportions according to claim 4, characterized in that: The precipitant is composed of ammonia water and water in a volume ratio of 1: (1-1.5).
6. The method for preparing a nanometer dual-phase high entropy zirconate material with nearly equal proportions according to claim 5, characterized in that: The aging time is 12-24 hours, the ball milling speed is 150-300 r / min, and the time is 2-4 hours.
7. The method for preparing a nanometer dual-phase high entropy zirconate material with nearly equal proportions according to claim 1, characterized in that: The high temperature calcination conditions are: 600-1600° C., and the time is 4-6 hours.
8. A nanometer dual-phase high entropy zirconate material with nearly equal proportions, characterized in that: Obtained by the preparation method according to any one of claims 1 to 7, the chemical formula is (La 0.2 Nd 0.2 G 0.2 Dy 0.2 Yb 0.2 )2Zr2O7, with nearly equal weight proportions of pyrochlore and fluorite phases.
9. The use of a nanometer dual-phase high entropy zirconate material with nearly equal proportions as claimed in claim 8, characterized in that: The prepared ceramic material is used for surface coating of hot end components of aero-engines and gas turbines.
10. The use of a nanometer dual-phase high entropy zirconate material with nearly equal proportions according to claim 9, characterized in that: The preparation process of the ceramic material is as follows: the high entropy zirconate material is subjected to PVA granulation, screening, compression molding and sintering treatment; wherein the amount of PVA added is 1-8% of the mass of the high entropy zirconate material; the compression molding pressure is 15-20 MPa, the pressurizing time is 100-120 s, the sintering temperature is 1500-1650° C., and the time is 8-10 h.
Citation Information
Patent Citations
A low thermal conductivity CMAS corrosion resistant high entropy zirconate ceramic material and its preparation method and application
CN115925417B
Doped and modified rare earth zirconate powder and preparation method and application thereof
CN112661511A
Zirconic acid rare earth-based high-entropy ceramic nanofiber as well as preparation method and application thereof
CN114751737A